2011
DOI: 10.1002/mrd.22011
|View full text |Cite
|
Sign up to set email alerts
|

The ability to achieve meiotic maturation in the dog oocyte is linked to glycolysis and glutamine oxidation

Abstract: We tested the hypothesis that meiotic competence of dog oocytes was tightly linked with donor follicle size and energy metabolism. Oocytes were recovered from small (< 1 mm diameter, n = 327), medium (1 – < 2 mm, n = 292) or large (≥ 2 mm, n = 102) follicles, cultured for 0, 24 or 48 h, assessed for glycolysis, glucose oxidation, pyruvate uptake, glutamine oxidation and then nuclear status. More oocytes (P < 0.05) from large follicles (37%) reached the metaphase II (MII) stage than from the small group (11%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…1; Table 1). Interestingly, dog and pig oocytes seem to utilize glucose as the primary energy substrate at a much higher rate than that of other species [32, 49], implying the species-specific differences in metabolic pattern of glucose in oocytes.…”
Section: Methodsmentioning
confidence: 99%
“…1; Table 1). Interestingly, dog and pig oocytes seem to utilize glucose as the primary energy substrate at a much higher rate than that of other species [32, 49], implying the species-specific differences in metabolic pattern of glucose in oocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, most mammalian species appear to rely on cumulus cells that contain an additional GLUT with high affinity to this substrate and high phosphofructokinase activity to convert glucose into readily utilized substrates (i.e., pyruvate, NADPH; (Sutton-McDowall et al, 2010;Biggers, et al, 1967). However, we have recently found that dog oocytes utilize glucose at a much higher rate than that of other species (Songsasen et al, 2012). This finding indicates that dog gamete may contain additional GLUT or high levels of glycolytic enzyme compared to those in other species.…”
Section: Glucose Is a Key Substrate For Providing Energy During Oocytmentioning
confidence: 81%
“…In order to correctly reference this scholarly work, feel free to copy and paste the following: N. Songsasen (2012). Energy Metabolism Regulating Mammalian Oocyte Maturation, Meiosis -Molecular Mechanisms and Cytogenetic Diversity, Dr. Andrew Swan (Ed.…”
Section: How To Referencementioning
confidence: 99%
“…Nuclear status assessments were carried out as previously described (Songsasen et al 2012). In brief, oocytes were fixed by placement into wells containing 1:3 acetic acid:ethanol solution for 48 h, then stained using aceto-orcein (1%…”
Section: Assessment Of Oocyte Nuclear Maturationmentioning
confidence: 99%